Cardiovascular Imaging of Biology and Emotion: Considerations Toward a New Paradigm. (August 2020) - Meadows, Judith L.; Shah, Samit; Burg, Matthew M.; Pfau, Steven; Soufer, Robert
Abstract : Central activation in response to emotion and cognitive stress induces perturbations in the heart and the peripheral vasculature that differ in physiology and clinical manifestations when compared with exercise-induced changes. While our conventional framework of epicardial coronary artery disease is foundational in cardiology, an expanded paradigm is required to address the cardiovascular response to mental stress (MS) and its associated risks, thus addressing the intersection of the patient's ecological and psychosocial experience with cardiovascular biology. To advance the field of MS in cardiovascular health, certain core challenges must be addressed. These include differences in the trigger activation between exercise and emotion, identification and interpretation of imaging cues as measures of pathophysiologic changes, characterization of the vascular response, and identification of central and peripheral treatment targets. Sex and psychosocial determinants of health are important in understanding the emerging overlap of MS–induced myocardial ischemia with microvascular dysfunction and symptoms in the absence of obstructive disease. In overcoming these critical knowledge gaps, integration of the field of MS will require implementation studies to guide use of MS testing, to support diagnosis of MS induced cardiac and vascular pathophysiology, to assess prognosis, and understand the role of endotying to direct therapy.